(3GdefJbi ef WHbGJ GdTaYjI ddCSfhi GdeJhaj SfI (B772 (3g`s - (3eMeO GdYQUi GdYQis; (3GdGSfhj , LeGd GdOjf CHh eMeO,J (B772 (3g` s ((3YHOGdQMef Hf YHOGdYRjR GHf ahRGf s)
(3ChdgG (B:s
(3hHYO , aEf GdTGaYj bO MUd dg aj CUMGHg ef GdSYGOI CehQ de JJab aj CUMGH ZjQg s
(3BNQgG (B:s
(3hai gPG GdbOQ caGjI hGddg Gdehab ddUhGH Ydi jO cGJHgG hefJbjgG eMeO GdYQUi GdYQi (B[(3cPG(B] (3ai efJUa LeGOi GdChd, SfI YTQ hKeGfeGFI s
(3HChdgG agQSJs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs